The Mediating Role Of Trust In The Relationship Between Religiosity, Financial Literacy, And Intention To Use Islamic Banking - Rosita Kusuma Wardani; Budi Sukardi (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
The growth of Islamic banking in Indonesia has not fully kept pace with the dominance of the Muslim population, as reflected in the sharp decline in the number of Islamic bank accounts in Surakarta, even though the majority of the population is Muslim. This study aims to analyze the influence of religiosity and financial literacy on the interest in becoming a customer of a sharia bank with trust as a mediating variable in generation Z Muslims in Surakarta. This quantitative-thematic study uses the Theory of Planned Behavior and Commitment-Trust Theory approaches to explain the formation of behavioral intentions and the role of trust in long-term customer-bank relationships. Data were collected through a five-point Likert questionnaire from 400 respondents selected using accidental sampling techniques, then analyzed using SEM‑PLS through SmartPLS 4. The results show that religiosity and financial literacy have a significant positive effect on trust, while the interest in becoming a customer is most strongly influenced by trust, followed by financial literacy, while the direct effect of religiosity is relatively weaker. Trust is proven to significantly mediate the influence of religiosity and financial literacy on interest, so that moral encouragement and new financial capabilities are converted into intentions when generation Z believes in the integrity and sharia compliance of the bank. These findings underscore the importance of an integrated Sharia financial literacy education strategy that enhances the image of Sharia compliance, transparency, and service quality to optimize the market potential of Generation Z in Muslim-majority areas.